The MOTILITY Mother-Child Cohort: a Danish prospective longitudinal cohort study of the infant gut microbiome, nutrition and bowel habits – a study protocol - Christian Mølgaard; Gladys Stolberg-Mathieu; Lasse Sommer Mikkelsen; Adam Duun Gottlieb; Henrik M. Roager (BMJ Open)
Introduction Concurrent with infants’ progression in dietary complexity and gut microbiome diversity, infants gradually change their defecation patterns during the first year of life. However, the links between bowel habits, the gut microbiota and early life nutrition remain unclear. The primary outcome is to characterise the gut microbiome development from birth to 1 year of age. Second, to investigate how bowel habits and nutrition in early life relate to the gut microbiome and metabolome during this period of life, and to explore how the development of the gut microbiome associates with host development.Methods and analysis The MOTILITY Mother-Child Cohort (MOTILITY) is a Danish prospective longitudinal cohort study enrolling up to 125 mother–infant dyads. Assessments occur at 36 weeks gestation (visit 1), birth (screening of infant) and 3, 6, 9 and 12 months (±2 weeks) post partum (visits 2–5). At visit 1, maternal anthropometrics, self-collected faecal and urine samples, and questionnaires on bowel habits and lifestyle are obtained. Between visits, infant faecal (biweekly), urine (monthly) and maternal breast milk (monthly until 6 months of age) samples are collected at home, and bowel habits and dietary intake are assessed biweekly by self-reported questionnaires. At visits 2–5, infant blood and saliva samples are collected, and anthropometric measurements are obtained. In addition, dietary intake is recorded thrice throughout the study period for mother and infant, respectively, and infant whole-gut transit time is estimated by sweet corn tests at 9 and 12 months of age. Birth, growth, motor development, sleep patterns, tooth development, overall health and well-being are assessed using questionnaires. Univariate and multivariate statistics will be applied to identify associations between the gut microbiome, early life nutrition and host physiology including bowel habits during the first year of life.Ethics and dissemination The MOTILITY study has been approved by the Research Ethics Committee for the Capital Region of Denmark (reference number: H-21063016). Selected results will be made available to the participants in the form of a summary document. Results will be published in peer-review journals and by means of national and international conferences.Trial registration number NCT05491161.